Inequality for power series with nonnegative coefficients and applications - Dragomir Silvestru Sever (Open Mathematics, 2015)
We establish in this paper some Jensen’s type inequalities for functions defined by power series with nonnegative coefficients. Applications for functions of selfadjoint operators on complex Hilbert spaces are provided as well.